Sandwich : the 'completest medieval town in England' : a study of the town and port from its origins to 1600 - Clarke, Helen; Sweetinburgh, Sheila; Jones, Bridgett E. A. (Oxbow Books, 2010)
To the casual visitor of today, Sandwich appears as simply a small inland market town on the bank of a modest river. But locals and historians have long known that in the Middle Ages it was a strategic and commercial seaport of great significance, trading with northern Europe and the Mediterranean and growing prosperous on this business. The medieval fabric of the town has been preserved to a remarkable extent, but historians and archaeologists have never agreed on quite where the first settlement was located. Nor has there been close study of what the surviving medieval buildings can tell us.